Short communication. The antifeedant activity of natural plant products towards the larvae of Spodoptera littoralis - Ballesta Acosta, M.C.=700 1 Pascual Villalobos, M.J.; Rodriguez, B.
(Es, En)
Ilus., 16 ref.
Keywords: SPODOPTERA LITTORALIS; PLAGAS DE PLANTAS; CONTROL DE PLAGAS; DITERPENO; CUMARINAS; FLAVONOIDES; METABOLITOS SECUNDARIOS; SPERMATOPHYTA; ESPAÑA